Judged and remembered trustworthiness of faces is enhanced by experiencing multisensory synchrony and asynchrony in the right order - Toscano, H. (2016)
This work builds on the enfacement effect. This effect occurs when experiencing a rhythmic stimulation on one's cheek while seeing someone else's face being touched in a synchronous way. This typically leads to cognitive and social-cognitive effects similar to self-other merging. In two studies, we demonstrate that this multisensory stimulation can change the evaluation of the other's face. In the first study, participants judged the stranger's face and similar faces as being more trustworthy after synchrony, but not after asynchrony. Synchrony interacted with the order of the stroking; hence trustworthiness only changed when the synchronous stimulation occurred before the asynchronous one. In the second study, a synchronous stimulation caused participants to remember the stranger's face as more trustworthy, but again only when the synchronous stimulation came before the asynchronous one. The results of both studies show that order of stroking creates a context in which multisensory synchrony can affect the trustworthiness of faces.